Global Knowledge Work: Diversity and Relational Perspectives - Gauthier, Carol-Anne (Relations industrielles / Industrial Relations, 2012)
Global Knowledge Work: Diversity and Relational Perspectives, edited by Katerina Nicolopoulou, Mine Karatas-Ozkan, Ahu Tatli and John Taylor, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Career development planning; Labor Unions; Skills; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Workplace diversity